Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1056/nejm199912093412402
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bisoprolol on Perioperative Mortality and Myocardial Infarction in High-Risk Patients Undergoing Vascular Surgery

Abstract: Bisoprolol reduces the perioperative incidence of death from cardiac causes and nonfatal myocardial infarction in high-risk patients who are undergoing major vascular surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
378
1
29

Year Published

2002
2002
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,334 publications
(415 citation statements)
references
References 14 publications
4
378
1
29
Order By: Relevance
“…12 These recommendations stem from the demonstration that perioperative treatment with betablockers decreased the incidence of cardiac complications and death in very high-risk vascular surgery patients. 13 Conversely, recent studies reporting the effects of preoperative beta-blockers on outcomes after non-cardiac (including vascular) surgery produced controversial results [14][15][16][17] and could not demonstrate risk reduction. The results of a meta-analysis after these trials suggested an increase in postoperative stroke.…”
mentioning
confidence: 99%
“…12 These recommendations stem from the demonstration that perioperative treatment with betablockers decreased the incidence of cardiac complications and death in very high-risk vascular surgery patients. 13 Conversely, recent studies reporting the effects of preoperative beta-blockers on outcomes after non-cardiac (including vascular) surgery produced controversial results [14][15][16][17] and could not demonstrate risk reduction. The results of a meta-analysis after these trials suggested an increase in postoperative stroke.…”
mentioning
confidence: 99%
“…2). When both mortality and morbidity data are considered, cardiac events occur in an estimated 1-5% of patients undergoing non-cardiac surgery, and the cardiovascular complication rate may reach 30% for patients undergoing vascular surgery 5,6 . In recent years the introduction of troponin assay for the diagnosis of perioperative MI [7][8][9][10][11][12][13][14] led to an apparent further increase in the frequency of perioperative MI from 1.4% with creatine kinase-MB assay to 6.6% 11 .…”
Section: Immentioning
confidence: 99%
“…On the basis of two studies 5,80 , the ACC/AHA task force on guidelines for non-cardiac surgery recommended perioperative beta-blockers for patients with preoperative stress test ischaemia having vascular surgery (class I recommendation) and for patients with established CAD, risk factors for CAD, or untreated hypertension having non-cardiac surgery (class IIa recommendation) 32 . In these two major studies, preoperative administration of beta-blockers titrated to a dose to achieve a resting heart rate of 50-60 bpm showed favourable effects on perioperative MI in high-risk patients undergoing major vascular surgery 5,80 .…”
Section: Perioperative Interventionsmentioning
confidence: 99%
See 2 more Smart Citations